Popularity, media and electability: study of Alfiansyah Komeng in the election of members of the Regional Representative Council (DPD) in West Java / Hendra, Mudiyati Rahmatunnisa and Ratnia Solihah - Hendra, Hendra; Rahmatunnisa, Mudiyati; Solihah, Ratnia (Faculty of Communication & Media Studies, 2024)
In 2024 Indonesia will again hold general elections to fill executive and legislative positions. One of the legislative member elections was to elect members of the Regional Representative Council (DPD) as the institution representing each province in Indonesia. An interesting phenomenon in this election was Alfiansyah Komeng's election as a DPD member representing West Java Province, surpassing the other candidates with the highest vote acquisition of 5,399,699 votes. Using a qualitative approach and data collection techniques through literature studies, the results showed that Komeng's electability was based on popularity, integrity, people's dissatisfaction with conventional politics, photos on ballot papers and the benefits of holding elections simultaneously. Meanwhile, according to the author, the media and the message conveyed are minor factors in Komeng's choice.